2010
DOI: 10.1124/dmd.110.035964
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Properties of Cholinesterase Inhibitors Donepezil, Tacrine, and Galantamine in Aged and Young Lister Hooded Rats

Abstract: ABSTRACT:Physiological alterations that may change pharmacological response accompany aging. Pharmacokinetic/pharmacodynamic properties of cholinesterase inhibitors (ChEIs) used in the treatment of Alzheimer's disease, donepezil, tacrine, and galantamine, were investigated in an aged Lister hooded rat model. Intravenous and oral 6-h blood sampling profiles in old (30 months old) and young (7 months old) rats revealed pharmacokinetic changes similar to those in humans with an approximately 40% increase in C max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
(42 reference statements)
2
39
1
Order By: Relevance
“…As reported by Goh et al (2011), administering GH orally in rats exhibited a high bioavailability (83 ± 13%) and 1.7:1 ± 0.2 brain/blood ratio 1 h after administration. However, GH is metabolized by hepatic cytochrome P450 enzymes, 460% of its metabolites are excreted via urine, and it has a short half-life (t 1/2 ) in rats ($1.9 h) (Mannens et al, 2002).…”
Section: Determination Of Ache Protein Level and Activity In Rat Brainssupporting
confidence: 61%
See 1 more Smart Citation
“…As reported by Goh et al (2011), administering GH orally in rats exhibited a high bioavailability (83 ± 13%) and 1.7:1 ± 0.2 brain/blood ratio 1 h after administration. However, GH is metabolized by hepatic cytochrome P450 enzymes, 460% of its metabolites are excreted via urine, and it has a short half-life (t 1/2 ) in rats ($1.9 h) (Mannens et al, 2002).…”
Section: Determination Of Ache Protein Level and Activity In Rat Brainssupporting
confidence: 61%
“…It has been reported by Goh et al (2011) that GH has a low-protein binding (about 18%) and a large volume of distribution (5.5 l/kg); which account for the accompanying cholinomimetic side effects due to its distribution to peripheral tissues such as nausea, vomiting, diarrhea, gastrointestinal cramping, and muscle weakness (Moffat et al, 2011). The significant weight loss and decreased food intake observed in the oral GH solution treated group reflect the potential side effects of administering GH orally which could be too intense in humans that the treatment should be discontinued (Hager et al, 2014).…”
Section: Clinical Signs Food Consumption and Body Weight Observationsmentioning
confidence: 99%
“…Based on this, and the absence of liver toxicity associated with various other inhibitors, tacrine-induced hepatotoxicity is believed to be mediated by immunologic mechanisms or mitochondrial injury that is unrelated to cholinesterase inhibition (Alfirevic et al, 2007). Because absorption of oral tacrine is about one-third of that following intravenous delivery (Goh et al, 2011), bioavailability of the dose chosen for our study is only slightly below that used by Ma et al (2003). We found no evidence of hepatic toxicity, which may have been mitigated by administering of tacrine as a slow infusion rather than bolus dosing.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, this observed effect with donepezil and rivastigmine was more pronounced in aged compared to young rats, which could be attributed to pharmacokinetic changes with age that influenced plasma levels of the two drugs. 48 It has been reported that the blood and brain concentrations of ChEIs are higher in aged than young rats. 48 …”
Section: Resultsmentioning
confidence: 99%